2020
DOI: 10.1101/2020.07.17.209452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR RNA-guided integrases for high-efficiency and multiplexed bacterial genome engineering

Abstract: Tn7-like transposons are pervasive mobile genetic elements in bacteria that mobilize using heteromeric transposase complexes comprising distinct targeting modules. We recently described a Tn7-like transposon from Vibrio cholerae that employs a Type I-F CRISPR-Cas system for RNA-guided transposition, in which Cascade directly recruits transposition proteins to integrate donor DNA downstream of genomic target sites complementary to CRISPR RNA. However, the requirement for multiple expression vectors and low over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 58 publications
3
56
0
Order By: Relevance
“…Lastly, transposaseassociated Type I-F systems have been shown to specifically insert synthetic "cargo" DNA up to 10 kb (kilobases) in length in E. coli with high fidelity, and thus holds promise as a technique to knock-in genes without requiring homologous recombination (Fig 4A)(66). Indeed, recent preprints have reported the use of transposaseassociated Type I-F systems for targeted insertion of antibiotic resistance genes in members of a microbial community, and multiplexed gene insertion in several medically and industrially important bacterial species (133,134).…”
Section: Editing and Applications Of Class 1 Crispr-cas Effectorsmentioning
confidence: 99%
“…Lastly, transposaseassociated Type I-F systems have been shown to specifically insert synthetic "cargo" DNA up to 10 kb (kilobases) in length in E. coli with high fidelity, and thus holds promise as a technique to knock-in genes without requiring homologous recombination (Fig 4A)(66). Indeed, recent preprints have reported the use of transposaseassociated Type I-F systems for targeted insertion of antibiotic resistance genes in members of a microbial community, and multiplexed gene insertion in several medically and industrially important bacterial species (133,134).…”
Section: Editing and Applications Of Class 1 Crispr-cas Effectorsmentioning
confidence: 99%
“…Common methods for chromosomal integration in bacteria include lambda RED based homologous recombineering 5 , Tn7 based transposition 6 , and phage integrase mediated recombination [7][8][9] . In addition, variations of these methods have been reported that combine CRISPR-Cas based targeting for improved efficiency 10 .…”
Section: Graphical Abstractmentioning
confidence: 99%
“…AAVs, on the other hand, have fewer adverse effects, but their payload capacity is limited to <5 kb (22). DNA transposases, such as Tn7 combined with catalytically inactive Cas9 for RNA-guided site-specificity, have been developed recently to perform targeted transgenesis of up to 10 kb of DNA, it is limited to prokaryotes (23)(24)(25)(26). Further, transposases exhibit high off-target integration (27) requiring extensive engineering to achieve precise transgenesis in human cells, mice, and other animals.…”
Section: Introductionmentioning
confidence: 99%